The Role of Islamic Economics in Overcoming Economic Inequality and Realizing Development in Indonesia - Delia Desvianti; Mardiana Safitri; Serliana; Zulfikar Hasan (Penerbit Hellow Pustaka, 2024)
Islamic economic development does not only measure the level of prosperity in the world, but is much more important than that, namely how prosperity will be in the afterlife. Economic inequality is a serious problem faced in many countries, including Indonesia. The application of Islamic economics can be a solution to overcome this problem with the principles of justice and fair distribution. Even though in Indonesia, Islamic economics is increasingly gaining attention with government initiatives and sharia financial institutions, there are still challenges such as a lack of understanding, regulations and policies that support the comprehensive development of Islamic economics. Research on the role of Islamic economics in overcoming economic inequality and realizing development in Indonesia is important to provide a deeper understanding of the implementation of Islamic economics and the steps that need to be taken for inclusive and sustainable development. The research method used in making this journal is the data selection method. Namely carrying out a systematic search for various journals relevant to the research topic using data analysis such as Google Scholar. In conclusion, the implementation of Islamic economics can be a sustainable and fair solution to overcome economic inequality. By applying the principles of justice, sustainability and transparency in economic practices, Indonesia can create a more just and sustainable society and achieve inclusive and sustainable development goals.